Accesibilidad del Hotel del Parque ubicado en el Cantón Samborondón - Saltos Alcivar, Karla Elisseth (2022)
This study seeks to answer the question Is the Hotel del Parque accessible? Where its general objective is to analyze the degree of accessibility that the Hotel del Parque has to verify if the facilities respond to the needs of people with reduced mobility, through descriptive research using the qualitative method, through observation and interview techniques. , for which the file for the collection of information corresponding to the Mintur was adapted, in such a way that a brief questionnaire was carried out in which, as a result, the establishment was obtained if it is accessible and has an adequate infrastructure in the facilities of the hotel, providing a quality service to this segment of people with reduced mobility.